THALASSEMIA LITERACY: INCREASING KNOWLEDGE OF ORPHAN ADOLESCENTS ON THALASSEMIA - Indiastuti, Danti Nur; Doman, Zahras Azimuth; Fatimah, Nurmawati; Nasution, Mhd Zamal; d'Arqom, Annette (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Thalassemia is the most common monogenic disease in Asia, including Indonesia that causes burdens for the government, patients, and families. As the sixth most non-communicable disease, thalassemia utilized IDR 600 billion in 2022 for more than 300 thousand cases. With, 3.8% of Indonesians carrying a mutation of thalassemia on their globin gene, this economic burden is projected will increase if no actions are taken. On the other hand, child marriage is reported to increase every year, including among orphans. Without proper knowledge and genetic testing on thalassemia, child marriage might contribute to the increasing of thalassemia patients. Thus, increasing knowledge on thalassemia among orphan adolescents is important. This community development uses several methods, including seminar, discussion, book, and poster, targeting the orphan adolescents (n= 40) in Mojokerta, East Java. A questionnaire on thalassemia was used to measure the knowledge, before and after the activity. The results show that the respondents have a moderate knowledge about thalassemia (median= 4 (0-9)), and increase to median=9 (3-10)) after the activities (p< 0.001). Even though overall knowledge is increased, several information including thalassemia is a genetic disease, not similar to blood cancer, not the only type of anemia (Q6), and how to diagnose thalassemia (Q9) still need to be emphasized. Taken together, direct and indirect approaches, such as seminar, discussion, book, and poster are effective in increasing thalassemia knowledge among orphan adolescents. These activities are more effective in targeting late adolescents, compared to early and middle adolescents. However, more effective methods are necessary to target Generation Z who are more familiar with the internet.